A comprehensive study on the mechanical properties of different regions of 8-week-old pediatric porcine brain under tension, shear, and compression at various strain rates. (2nd January 2020) - Li, Zhigang; Ji, Cheng; Li, Dapeng; Luo, Rutao; Wang, Guangliang; Jiang, Jinzhong
Abstract: Young porcine brain is often used as a surrogate for studying the mechanical factors affecting traumatic brain injury in children. However, the mechanical properties of pediatric brain tissue derived from humans and piglets are very scarce, and this seriously detracts from the biofidelity of the developed finite element (FE) models of the pediatric head/brain. The present study addresses this issue by subjecting the cerebrum (white matter and gray matter), cerebellum, and brainstem specimens derived from 8-week-old piglets to tension and shear testing at strain rates of 0.01, 1, and 50/s. The experimental data are combined with the corresponding data derived from a previous study under compression to obtain comprehensive stress-strain curves of the pediatric porcine cerebrum, cerebellum, and brainstem tissue specimens. In general, the average stress level of the white matter is somewhat higher than that of the gray matter under the tension, shear and compression conditions, however, this difference does not reach a significant level. The stiffness of the cerebellum and the cerebrum does not differ significantly under tension and shear conditions, but the stiffness of the cerebellum is greater than that of the cerebrum under compression. The brainstem has significantly higher stiffness than the cerebrum and the cerebellum under all loading modes. In addition, the mechanical properties of brain tissue exhibit significant strain-rate dependences. With increasing strain rate from 0.01/s to 50/s, the average stress at a strain of 0.5 for all of the brain tissue increased by about 2.2 times under tension, about 2.4 times under shearing and about 2.2 times under compression. The variations in the stress as a function of the strain rate for brain tissue specimens were well characterized by exponential functions at strains of 0.25 and 0.5 under all three loading modes. The results of this study are useful for developing biofidelic FE models of the pediatric brain.